ANALISIS PENGENDALIAN PERSEDIAAN PRODUK CHITATO STUDI KASUS : PT. KEMBAR PUTRA MAKMUR DENPASAR-BALI - Wikantari, Ni Putu Candra; Satriawan, I Ketut; Sedana Yoga, I Wayan Gede (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 6 No 4 (2018): DesemberDO - 10.24843/JRMA.2018.v06.i04.p07, 2018)
This study aims to apply the EOQ method for planning Chitato product orders at PT. Kembar Putra Makmur. Data collection is done by interviewing. The results showed that the highest supply of Chitato 15 grams of Chitato Beef Barbeque with a purchase frequency of 20 orders in one year, with the number of orders was 4,928 boxes, the amount of Safety Stock was 3,364 boxes, and the company retured to oder (Reorder Point) when inventory reaches 4,676 boxes. Companies should use the Economic Order Quantity (EOQ) method, Safety Stock, and Reorder Points in processing and controlling inventory to avoid stock out. Keywords : inventory control, chitato, Economic Order Quantity (EOQ), Safety Stock, and Reorder Point